The Relationship Between Nurse Response Time In Treating Open Fractur Patients And The Risk Of Hypovolemic Shock In The Emergency Room Of Grandmed Hospital Lubuk Pakam - Tati Murni Karokaro; Amy Vivi Insani Alja (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Introduction:Open fractures are bone injuries involving skin disruption, leading to direct bone exposure and a high risk of contamination. Emergency care reports indicate that around 50% of trauma patients die en route to the hospital, 35% due to severe injuries. Timely nursing response is crucial in early emergency management, especially in open fractures. This study aimed to assess the association between nurses' response time and the risk of hypovolemic shock in patients with open fractures. Methods:A descriptive correlational study was conducted from September to October 2024 at the Emergency Department of Grandmed Hospital, Lubuk Pakam. Thirty-one nurses were selected using total sampling. Data were obtained through structured observations of eligible nurses. Results: Delayed response was observed in 32.3% of nurses, with hypovolemic shock occurring in 32.3% of patients. Fisher’s Exact Test revealed a significant association between nursing response time and hypovolemic shock risk (p = 0.040). Discussion: Delayed nursing interventions were significantly linked to increased hypovolemic shock risk. The findings underscore the need for effective leadership and prompt nursing action to prevent complications.